2020
DOI: 10.3847/1538-4357/ab5fdc
|View full text |Cite
|
Sign up to set email alerts
|

HST Imaging of the Ionizing Radiation from a Star-forming Galaxy at z = 3.794

Abstract: We report on the HST detection of the Lyman-continuum (LyC) radiation emitted by a galaxy at redshift z = 3.794, dubbed Ion1 (Vanzella et al. 2012). The LyC from Ion1 is detected at restframe wavelength λλ 820∼890Å with HST WFC3/UVIS in the F410M band (m 410 = 27.60 ± 0.36 m AB , peak SNR = 4.17 in a circular aperture with radius r = 0.12") and at λλ 700∼830Å with the VLT/VIMOS in the U-band (m U = 27.84 ± 0.19 m AB , peak SNR = 6.7 with a r = 0.6" aperture). A 20-hr VLT/VIMOS spectrum shows low-and high-ioniz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 130 publications
1
35
0
Order By: Relevance
“…f c and Lyα escape fraction have also been determined to predict LyC escape fractions at low redshift (Chisholm et al 2018;Gazagnes et al 2018). Additionally, HST analysis of a spatially resolved FUV colour map has shown that bluer colours are coincident with LyC escape, demonstrating that favorable H I and dust configurations lead to LyC escape (Ji et al 2020). Finally, the Lyα kinematics of a strongly-leaking z ∼ 3 galaxy have demonstrated the consistent geometry of LyC and Lyα escape (Vanzella et al 2020).…”
Section: F Esc Absmentioning
confidence: 92%
“…f c and Lyα escape fraction have also been determined to predict LyC escape fractions at low redshift (Chisholm et al 2018;Gazagnes et al 2018). Additionally, HST analysis of a spatially resolved FUV colour map has shown that bluer colours are coincident with LyC escape, demonstrating that favorable H I and dust configurations lead to LyC escape (Ji et al 2020). Finally, the Lyα kinematics of a strongly-leaking z ∼ 3 galaxy have demonstrated the consistent geometry of LyC and Lyα escape (Vanzella et al 2020).…”
Section: F Esc Absmentioning
confidence: 92%
“…In recent years, direct 𝑓 esc studies have largely concentrated on two redshift windows set by available UV instrumentation -one at 𝑧 ≈ 0.3 where Lyman continuum (LyC) is accessible to HST/COS (e.g., Izotov et al 2016aIzotov et al , 2018bIzotov et al , 2021aWang et al 2019Wang et al , 2021, and another at 𝑧 ≈ 2 − 4 accessible to ground-based facilities and HST/WFC3 UVIS (e.g., Jones et al 2018;Smith et al 2020;Ji et al 2020;Meštrić et al 2020;Marques-Chaves et al 2021;Davis et al 2021;Prichard et al 2021). The 𝑧 ≈ 0.3 COS efforts were first undertaken at a time when only a handful of robust LyC leakers had been identified, and it was unclear whether LyC leakage even occurred among the 0.5𝐿 * galaxies for which 𝑓 esc measurements were feasible (e.g., Izotov et al 2016a,b).…”
Section: Introductionmentioning
confidence: 99%
“…Strong LyC leakage has been confirmed from a number of galaxies at z ∼ 0-4, with inferred fesc from a few per cent to over 50 per cent (e.g. Vanzella et al 2012Vanzella et al , 2016Vanzella et al , 2020Izotov et al 2016bIzotov et al ,a, 2018Fletcher et al 2019;Rivera-Thorsen et al 2019;Ji et al 2020). Most of them are compact, extreme starburst galaxies that are thought to be analogs of typical star-forming galaxies in the reionization era.…”
mentioning
confidence: 98%